The Effect of Counseling with Video Media On Diarrhea Prevention Knowledge: Pre-Experimental Study of the Desa Kresek, Kabupaten Tangerang - Putri, Shavira Wadya; Ernawati, Kholis; Atmalia, Khafifah Puja; Karidza, Bilqish; Ahmad, Lulu Nuraviah; Triangga, Riyan; Febylia, Nanda (Lembaga Penelitian Universitas YARSI, 2023)
Introduction: Low knowledge of diarrhea prevention is why diarrhea rates are still high in Indonesia. There have been many ways to increase public knowledge related to diarrhea prevention, one of which is by conducting counseling using video media. This study aimed to determine the effect of video media counseling on knowledge of diarrhea prevention: a pre-experimental study in the community of Kresek Village, Tangerang Regency. Methods: Thei researchi designi wasi pre-experimenti onei groupi pre-test-post-test.i Thei populationi wasi thei community in Kampung Nambo, Kresek District, Tangerang Regency, Banten Province. The study was conducted in January 2023. Criteria for respondents over 13 years of age. The study sample amounted to 40 people taken by consecutive sampling, which was taken for seven days. The intervention was conducted with education using video media titled